(untitled) (Bisanzio e l’Occidente, 2019)
Unlike what happened in the Byzantine world, the history of thought in the Latin West testifies to a continuous effort to establish with the greatest possible precision a boundary between the sphere of competence of temporal rulers and the jurisdiction of spiritual rulers. As a result, in the period between the end of the fifth century and the fourteenth the doctrine of the double vicariate of Christ was used in defensive function, in turn, by the supporters of both powers, who appealed alternatively to this doctrine to curb any attempt to go beyond their sphere of competence by the pope, the emperor or a national monarch.